Surgical reconstruction of a maxilla after tumour resection with a heterologous equine bone block created with CAD/CAM procedure: a case report. (1st April 2014) - Pistilli, R.; Checchi, V.; Nisii, A.; Marcelli, V.; Felice, P.
Abstract: This case report describes a successful post‐tumour surgical reconstruction of a complete maxilla resection in a 62‐year‐old man, using an equine bone block [pre‐shaped using computer aided design/computer aided manufacturing (CAD/CAM) procedure] as grafting material. Computerised tomographic scans taken 5 months after the reconstructive surgery showed good reconstruction and dimensional augmentation of the lost bone. One year after surgery, the patient showed a great improvement in the emergence profile of the middle part of the face. The use of an equine bone block, pre‐shaped using CAD/CAM system, for alveolar ridge reconstruction, seems to be a valuable alternative to autograft. This technique could significantly shorten the actual surgical procedure for the patient and may result in a better fit of the graft than chair‐side preparation may allow.